Description of service satisfaction level outpatient nursingin hospital outpatient Poly Elisabeth Medan 2022 - Karo, Mestiana Br; Sigalingging, Vina YS; Siregar, Hermina (Institute of Accounting Research and Novation (IARN), 2023)
Satisfaction is a feeling of pleasure or disappointment that someone feels after comparing performance with what is expected, if the performance is below expectations then the customer is not satisfied, but on the contrary if it meets expectations the customer feels satisty and if the performance exceeds expectations the customer feels very satisfied and happy. This study aims to identify a description of the level of satisfaction of outpatients at the Outpatient Polyclinic of Elisabeth Hospital Medan in 2022. The data collection method used in this study is the primary data method. become respondents who meet the criteria for a total sample of 37 respondents. The instrument used is a satisfaction questionnaire. The results shows that the reliability (reliability) in the Outpatient Clinic of Santa Elisabeth Hospital Medan is very satisfied with 33 respondents (89.2%), assurance (guarantee) very satisfied, 35 respondents (94.6%), tangibles (reality) very satisfied. as many as 37 respondents (100%), empathy (empathy) very satisfied as many as 35 respondents (94.6%), responsiveness (responsibility) very satisfied as many as 35 respondents (94.6%). Therefore, nurses can maintain the level of satisfaction of nursing services in outpatients and increase a sense of care, the responsibility of nurses to patients, nursing services in outpatients. Bibliography (2008-2022)